Relationship Between General Self-Efficacy and Quality of Life Among Elderly Living in Chaharmahal Bakhtiari Nursing Homes - Ladan Naseh; Mohammad Heidari (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives Reduction of physical and mental strength along with several diseases in aging severely diminishes elder people's quality of life. Meanwhile, self-efficacy can improve quality of life. We aimed to assess the relationship between self-efficacy and quality of life in elderly living in nursing homes. Methods & Materials In this cross-sectional descriptive study, 87 elder people living in Charmahal Bakhtiari nursing homes were recruited by census. Data were collected by General Self-Efficacy Scale (GSE-10) and Short Form Quality of Life (SF-36) and then analyzed using independent t-test, ANOVA, Kruskal-Wallis and regression analysis.  Results 69% of the participants had low level of general self efficacy (22.95±8.02). 65.5% of them had low score in total quality of life (41.56±18.59). A significant positive association was found between general self-efficacy and physical functioning (r=0.701), Physical role performance (r=0.350), emotional role performance (r=0.354), social functioning (r=0.821), psychological health (r=0.722), energy and vitality (r=0.749), body pain (r=0.783), general health (r=0.597) subscales and also with overall quality of life (r=0.797) (P<0.01). Conclusion Poor quality of life in elder people who live in elderly nursing homes is an important finding that needs special attention. Because of the significant correlation between general self-efficacy and different subscales of elder’s quality of life in this study, it is suggested that nurses can design and execute appropriate interventions to promote these peoples’ self-efficacy and quality of life.